The Influence of Service Quality and Product Quality Towards Customer Satisfaction Beautiful Photo Studio Tuban - Suwardana, Hendra; Yusuf, Muhammad (INNOVATION RESEARCH JOURNAL, 2025)
This study highlights the growing awareness among customers regarding the significance of service and product quality in shaping their satisfaction. As a result, businesses, including Indah Photo Studio Tuban, strive to enhance both aspects to meet customer expectations. The study aims to analyze: (1) the partial effect of service quality on customer satisfaction, (2) the partial effect of product quality on customer satisfaction, and (3) the combined effect of both factors on customer satisfaction. Using an incidental sampling technique, 58 respondents participated in the study. Findings reveal a positive and significant impact of service quality on customer satisfaction, supported by a t-value of 3.963 (greater than 2.004) and a probability value of 0.000 (<0.05). The contribution of service quality to customer satisfaction is 38.2%. Similarly, product quality significantly affects customer satisfaction, with a t-value of 5.595 (greater than 2.004) and a probability of 0.000 (<0.05). The contribution of product quality to satisfaction is 53.9%. When analyzed simultaneously, service and product quality have a strong combined impact on customer satisfaction, with an F-value of 64.817 (greater than 3.156) and a probability of 0.000 (<0.05). Their combined contribution to satisfaction is 70.2%.